'Graduate Blues': Considering the Effects of Inverted Symbolic Violence on Underemployed Middle Class Graduates. (April 2017) - Burke, Ciaran
The understanding of social reproduction, from a Bourdieusian perspective, is that the dominant typically reproduce their position in social space through various apparatus, such as the education system, to the detriment of the dominated group, who are unable to leave their own position, characterised by inequality and suffering. A key tool in achieving social reproduction is the process of symbolic violence; however, this article considers the effects of inverted symbolic violence. By following the trajectories of two middle class university graduates, this article will demonstrate the detrimental effect inverted symbolic violence has on their graduate employment trajectories. Respondents are depicted as having inflated subjective expectations incompatible with current objective realities within the labour market, resulting in a relatively downward, or unsuccessful, trajectory.